O Auto-Esvaziamento do Logos uma análise da Cristologia Quenótica de Gottfried Thomasius - MEDEIROS, CHRISTIAN BRIALLY DE (2006)
To present dissertation it turns on the theme of the German Lutheran theologian's of the nineteenth century kenotic christology, Gottfried Thomasius, as an answer possibility to the problem of the two natures, divine and human, in Jesus Christ's person. Taking into account the traditional christology as formulated by the Council of Chalcedon the proposer of the kenoticism suggests that Logos, eternal Son of God, solemnity-empty-if voluntarily of their no-essential attributes or those that possess a direct relationship with the nature, in other words, the omnipresence, the omnipotence and the omniscience. The Formula of Chalcedon is constituted in the object for which Thomasius promotes a reinterpretation with the intention of turning her intelligible to time, then the dissertation to offer the base of construction of such theory. However, it is shown as a concerned theologian in preserving their traditions before the criticism of the century XIX. It also comes the subsequent development of the kenotic christology in that the subsequent theologians diverge in some points, they develop other, they react and they try to overcome problems and initial difficulties of the theory as formulated by Thomasius. It offers innovative solutions ahead to the christological problem of the incarnation with John Hick's support that suggests an approach to the theme of the incarnation by the use of the theological speech as religious metaphor with pluralist perspective. It is also Roger Haight at the end, proposing a symbolic approach of the christological formulation of Chalcedon as middle of emphasizing positive aspect and this done from a comprehensible way to the present time.